2021
DOI: 10.3389/fpls.2021.716855
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of NtSOS2 From Halophyte Plant N. tangutorum Enhances Tolerance to Salt Stress in Arabidopsis

Abstract: The Salt Overly Sensitive (SOS) signaling pathway is key in responding to salt stress in plants. SOS2, a central factor in this pathway, has been studied in non-halophytes such as Arabidopsis and rice, but has so far not been reported in the halophyte Nitraria tangutorum. In order to better understand how Nitraria tangutorum acquires its tolerance for a high salt environment, here, the NtSOS2 was cloned from Nitraria tangutorum, phylogenetic analyses showed that NtSOS2 is homologous to the SOS2 of Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It has been reported that in addition to being involved in the response to salt stress, the SOS2 gene can also be induced by abscisic acid (ABA) and various abiotic stresses and may have a variety of physiological functions [24]. So far, the SOS2 gene has been functionally characterized in a variety of plant species, and it has been shown that overexpression of SOS2 can improve the salt tolerance of different transgenic plants [25][26][27]. Unfortunately, research on the function of the SOS2 gene in mulberry is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in addition to being involved in the response to salt stress, the SOS2 gene can also be induced by abscisic acid (ABA) and various abiotic stresses and may have a variety of physiological functions [24]. So far, the SOS2 gene has been functionally characterized in a variety of plant species, and it has been shown that overexpression of SOS2 can improve the salt tolerance of different transgenic plants [25][26][27]. Unfortunately, research on the function of the SOS2 gene in mulberry is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…SOS2 exists as a form of protein kinase in the SOS signaling pathway, which in turn activates SOS1 to bring about sodium ion homeostasis and salt tolerance (Ali et al, 2021). SOS3, which encodes an EF-handed Ca 2+ binding protein, can sense calcium signals elicited by salt stress, interact with SOS2, and activate SOS2 (Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of the SOS2 gene improved salinity tolerance in different transgenic plants. In a recent study, Zhu et al (2021) reported that the overexpression of SOS2 from the halophytic plant Nitraria tangutorum enhanced salinity tolerance in Arabidopsis. However, functional genomics studies for assessing the effect of overexpression and knockdown of OsSOS2 on the agronomic features of rice under salinity and drought are not available.…”
Section: Introductionmentioning
confidence: 99%